Implementasi Manajemen Pendidikan Karakter Berbasis Adab di Sekolah Dasar Islam Terpadu - Effendi, Mardian; Warsah, Idi; Bahri, Syaiful (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The implementation of the National Curriculum character education program has not achieved maximum results, because the value of religious manners has been eroded by the growing influence of technology, culture, and the times, we can see this in today's students who have not been able to apply the values of polite culture both in the application of speech, dress and behavior patterns, while manners are the main staple of the Islamic generation before studying science. The adab-based character education program can restore the character of Indonesian students who have noble morals by upholding polite culture. This study aims to describe and analyze in depth the Implementation of Adab-Based Character Education Management at Khoiru Ummah Integrated Islamic Primary School. This research uses a Qualitative approach. Data sources were obtained from the Principal, Vice Principal of Curriculum, Vice Principal of Student Affairs, Vice Principal of Islamic Personal Development, Student Guardians, and Students of SDIT Khoiru Ummah. Data collection techniques include observation, interviews, documentation studies, and data analysis using Milles and Huberman models. The results of this study indicate that the implementation of adab-based character education management at SDIT Khoiru Ummah through a program strategy based on the Integrated Islamic School Network (JSIT) in the BPI Islamic Personal Development program, by instilling ukhrowi values in every learning process and extracurricular activities through management patterns of Planning, Actuating and Controlling as an effective implementation of adab-based character education management